Livestock-wealth inequalities and uptake of crop cultivation among the Maasai of Kenya and Tanzania - Nkedianye, D.K.; Ogutu, Joseph O.; Said, Mohammed Yahya; Kifugo, S.C.; Leeuw, Jan de; Gardingen, P.V.; Reid, Robin S. (Elsevier, 2019)
We examine livestock-wealth inequality by gender and age of the household head among Maasai households located in areas of contrasting land tenure and land productivity in the Amboseli, Athi-Kaputiei and Maasai Mara regions of Kenya and Tarangire-Manyara Region of Tanzania. We also investigate whether livestock-poor households are more likely to diversify their livelihood options from pastoralism to include crop cultivation. Livestock wealth inequality was high in each of the four sites. Surprisingly, the Tarangire-Manyara site in Tanzania had the highest levels of inequality despite the fact that Tanzania had recently had a socialist political system while Kenya had been capitalistic since independence in 1963. The disparities in livestock assets between the rich and the poor households were lowest in the Maasai Mara site. Also, there was no direct relationship between low livestock wealth and the probability that a household would take up crop cultivation. However, areas under cultivation were the largest in Tarangire-Manyara and the lowest in Amboseli, possibly reflecting the influence of land tenure policy in Tarangire-Manyara and low rainfall in Amboseli. Most male headed households had more livestock wealth than female headed households. In Maasailand, high livestock-wealth inequalities and a growing restriction on livestock mobility, compounded with internal and external population pressures and land fragmentation, are likely to reduce pastoral resilience to droughts that are becoming more frequent and severe due to a warming global climate and widening climatic variability.